Review of Medium-Voltage Switchgear Fault Detection in a Condition-Based Monitoring System by Using Deep Learning - Alsumaidaee Y.A.M.; Yaw C.T.; Koh S.P.; Tiong S.K.; Chen C.P.; Ali K. (MDPI, 2023)
Condition based maintenance; Condition monitoring; Deep learning; Electric power transmission networks; Fault detection; Testing; Ultrasonic applications; 'current; Arcing; Condition-based monitoring; Deep learning; Energy distribution networks; Faults detection; Medium voltage; Medium voltage switchgears; Monitoring system; Power energy; Partial discharges